A Comparative Study Between the Effectiveness of 980 nm Photobiomodulation Delivered by Hand-Piece With Gaussian vs. Flat-Top Profiles on Osteoblasts Maturation - Hanna, Reem; Agas, Dimitrios; Benedicenti, Stefano; Ferrando, Sara; Laus, Fulvio; Cuteri, Vincenzo; Lacava, Giovanna; Sabbieti, Maria Giovanna; Amaroli, Andrea (Frontiers in Endocrinology, 2019)
Photobiomodulation (PBM) is a clinically accepted tool in regenerative medicine and dentistry to improve tissue healing and repair and to restore the functional disability. The current in vitro study aimed to investigate the photobiomodulatory effects of 980 nm wavelength (the real energy at the target: ~0.9 W, ~0.9 W/cm2, 60 s, ~55 J/cm2 and a single energy ~55 J in CW) on MC3T3-E1 pre-osteoblast, delivered with flattop profile in comparison to the standard profile. The laser groupings and their associated energies were: Group 1 - once per week (total energy 110 J); Group 2 - three times per week (alternate day) (total energy 330 J); Group 3 - five times per week (total energy 550 J). The metabolic activity and the osteoblasts maturation were analyzed by alkaline phosphatase assay, alizarin red S histological staining, immunoblot and/or double immunolabeling analysis for Bcl2, Bax, Runx-2, Osx, Dlx5, osteocalcin, and collagen Type 1. Our data, for the first time, prove that laser irradiation of 980 nm wavelength with flat-top beam profile delivery system, compared to standard-Gaussian profile, has improved photobiomodulatory efficacy on pre-osteoblastic cells differentiation. Mechanistically, the irradiation enhances the pre-osteoblast differentiation through activation of Wnt signaling and activation of Smads 2/3-βcatenin pathway.